Physicochemical and biological characteristics of the nanostructured polysaccharide‐iron hydrogel produced by microorganism Klebsiella oxytoca. (8th November 2016) - Kianpour, Sedigheh; Ebrahiminezhad, Alireza; Mohkam, Milad; Tamaddon, Ali Mohammad; Dehshahri, Ali; Heidari, Reza; Ghasemi, Younes
Abstract : There is an increasing interest in the nanostructured polysaccharide‐iron hydrogel produced by Klebsiella oxytoca . Critical physicochemical and biological characteristics of these nanostructures should be revealed for biomedical applications. Accordingly, an iron reducing strain K. oxytoca, which synthesizes biogenic polysaccharide‐iron hydrogel nanoparticles, known as Fe (III)‐exopolysaccharide (Fe‐EPS) was isolated from a mineral spring. For microbiological identification purpose 16S rRNA sequence analysis and different morphological, physiological, and biochemical characteristics of the isolate were studied. Critical physicochemical and biological characteristics of the produced Fe‐EPS were evaluated using transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectroscopy, X‐ray crystallography (XRD), vibrating sample magnetometer (VSM). In addition, for the first time, Fe‐EPS which synthesized by K. oxytoca was evaluated by dynamic light scattering (DLS), thermo gravimetric analysis (TGA), and cytotoxicity assay. TEM micrographs showed that the biogenic Fe‐EPS is composed of ultra‐small (about 1.8 nm) iron oxide nanoparticles (IONs) which are trapped in a polysaccharide matrix. The matrix was about 17% (w/w) of Fe‐EPS total weight and provided a large negative charge of −71 mV. Interestingly, Fe‐EPS showed a growth promotion effect on hepatocarcinoma cell line (Hep‐G2) and 36% increase in the percentage of viability was observed by 24 h exposure to 500 μg ml −1 Fe‐EPS.